The IASLC/ATS/ERS classification of lung adenocarcinoma-a surgical point of view - Fang, Wentao; Xiang, Yangwei; Zhong, Chenxi; Chen, Qunhui (Journal of Thoracic Disease, 2014)
Adenocarcinoma has become the most common histologic type of lung cancers. Ground glass nodules (GGN), most of them early stage noninvasive or minimally invasive adenocarcinomas (MIA), have been encountered more frequently with the application of computed tomography (CT) screening. The International Association for the Study of Lung Cancer (IASLC)/American Thoracic Society (ATS)/European Respiratory Society (ERS) histologic lung adenocarcinoma classification combines radiologic, histologic, clinic, and molecular features to form a diagnostic approach for different subgroups of diseases. One of the major focuses of this new classification is the introduction of adenocarcinoma in situ (AIS) and MIA, to replace the old term of bronchioloalveolar carcinoma (BAC). Not all GGNs are malignant lesions that should be surgically resected upon first presentation. A management approach different to solid nodules has been suggested based on the understanding that these lesions tend to have a more indolent nature. Hasty intervention should be avoided and potential surgical risks, radiation exposure, patient psychology, and socio-economical burden must be balanced comprehensively before surgery is decided upon. In the mean time, surgical issues concerning extent of resection and lymphadenectomy should also be carefully contemplated once intervention is deemed necessary. Extremely good prognosis with a near 100% disease-free survival could be expected when a pure GGN is completely resected. This has led to re-evaluation of sublobar resections, including both segmentectomy and big wedge resection, for small (≤2 cm) less invasive histology (AIS or MIA) appearing as GGN on CT scan. Evidences are accumulating that these limited resections are oncologically equivalent to standard lobectomy. And extensive lymph node dissection may not have additional staging or prognostic benefit. These would add new meaning to the contemporary definition of minimally invasive surgery for lung cancers. Overall, joint effort from a multiple disciplinary team is imperative, and decision making should be based on both anatomical and biological nature of the disease.